Measuring knowledge sharing in open source software development teams - LONG, Y. (Institutional Knowledge at Singapore Management University, 2007)
The study provides an approach to measure the extent of knowledge sharing in Open Source Software (OSS) development in terms of two aspects: the quality of knowledge sharing which is indicated by the helpfulness of the messages, and the quantity of knowledge sharing which is indicated by the volume of the messages. The study developed a computer-aided content analysis program to assess the helpfulness of the messages based on a set of keywords and the length of the messages. The approach was applied to measure the extent of knowledge sharing of 150 OSS projects. The results further confirmed that the two measures (i.e., helpfulness of messages and volume of messages) assess different aspects of knowledge sharing. Another contribution of this research is the computer-aided content analysis program, which has been shown to be effective and reliable and can be applied in future research.